المؤسسات الناشئة التوجه الريادي الجديد للطلبة الجامعيين - جبريط أحمد; عيشوش محمد الحافظ (جامعة الوادي University Of Eloued, 2024)
This study aims to know the orientation of university students through the motives that motivate them to establish a startup, in other words, to identify the characteristics necessary for the practice of entrepreneurship. This study was conducted on a targeted sample consisting of 76 male and female students from Echahid Hamma Lakhdar University of El Oued. A questionnaire was used as a data gathering tool, and a set of statistical methods and spss program, version 26 to process data and test hypotheses. A set of results have been reached, among them, we mention the following: A great proportion of the students showed positive response regarding the desire to establish a start-up institution. Students have creative ideas that they want to embody on the ground by seizing opportunities, but what is noticed is that the majority of students do not have sufficient knowledge of research and development centers.
Start up The new entrepreneurial orientation for university students Case study of Valley University Students
Keywords: طلبة جامعيين; مؤسسة ناشئة; ريادة الأعمال; مراكز البحث والتطوير; University students; Start-up enterprise; Entrepreneurship Research and development Centers